Treatment of Carbide Sludge from an Acetylene Production Plant by Flocculation - Agamuthu, Pariatamby; Ibrahim, Shaliza (SIRIM Berhad, 2001)
The treatment of carbide sludge by the flocculation is a relatively new technique, which is considered more environmentally and economically favourable compared to a pond system commonly practiced in local industries. Tests were carried out in a 15,000 litre vessel using 200 or 400 ppm solid or liquid flocculent, with the slurry/flocculant mixture fed either from the top or bottom. The targeted sludge concentration or "alkalinity" of 25% solid, which is the value desired for commercial purposes, was most optimally achieved with 200 ppm liquid flocculant, fed from the bottom. The sludge thus formed, with a pH of 12.9 is readily purchased by other countries for neutralizing acidic wastes. In addition to the sale of sludge, implementation of the flocculation system eliminates land-filling costs and reduces water usage through the possibility of water recyling.